PERSONAL AND CONTEXTUAL FACTORS AND ACADEMIC RESILIENCE OF LECTURERS AT STATE AND PRIVATE ISLAMIC UNIVERSITIES DURING PANDEMIC - Khalilah, Khalilah (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
This article discusses what factors can potentially determine the academic toughness of lecturers in the PTKIN and PTKIS environments in Indonesia during the Covid-19 pandemic. To that end, this article adapts Martin and Marsh's concepts of academic resilience and teacher resilience developed by Beltman and the ideas of Beltman et al., Mansfield et al., and Alyev et al., on the determinants of academic toughness. Survey data from lecturers at PTKIN and PTKIS were analyzed using descriptive statistical analysis and produced the following findings. The academic toughness of potential PTKIN and PTKIS lecturers is determined by the following two groups of factors, namely personal and contextual factors. Trust or belief in self (self-efficacy) and self-respect (self-respect) as lecturers to achieve the learning outcomes they plan to achieve are two important personal factors that can determine the academic toughness of the PTKIN and PTKIS lecturers. In addition, this article also describes six types of potential contextual factors that determine their academic toughness. Both types of groups of factors have the potential to determine their academic resilience in carrying out academic activities, especially in the context of education and teaching that they carry out during the Covid-19 pandemic.